THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON PERFORMANCE EMPLOYEE THROUGH MOTIVATION WORK AS AN INTERVENING VARIABLE IN NELONGSO FRIED CHICKEN - Deccasari, Dwi Danesty; Andini, Lydia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This study aims to analyze the influence of work environment and organizational culture on employee performance through work motivation as an intervening variable. The study was conducted on employees of Ayam Goreng Nelongso in Malang City. The research method used is quantitative causal with a survey approach. Data were collected through questionnaires distributed to 42 respondents, using simple random sampling techniques. Hypothesis testing was carried out using multiple linear regression analysis and path tests to identify direct and indirect relationships between variables. The results of the study indicate that the work environment has a significant effect on employee performance, both directly and through work motivation. However, organizational culture does not have a significant effect on employee performance, either directly or through work motivation. Work motivation also cannot act as a significant mediator between the work environment or organizational culture on employee performance. This study provides practical implications that improving the work environment is a priority to improve employee performance, while strengthening organizational culture needs to be further evaluated to improve its effectiveness.